THE SCALES FOR ACCEPTANCE, USABILITY, AND SATISFACTION FOR WEB-BASED MONITORING AND SUPPORT SYSTEMS - Nazire Burcin Hamutoglu; Özlem Güngören-Canan; İbrahim Duman; Mehmet Barış Horzum; Mübin Kıyıcı; Özcan Erkan Akgün (Informascope, 2019)
The purpose of this study is to develop three scales to assess some features of a web-based monitoring and support system for internship processes of trainees which were named Monitoring and Support System (SIDES). These scales are: "SIDES Satisfaction Scale", "SIDES Acceptance Scale", and "SIDES Usability Scale". We developed these scales as an assessment model within the scope of a project. In development phases, the scopes and the names of the scales were formed by results of the literature review. Satisfaction, acceptance and usability scales have item pools with 6, 17 and 27 questions respectively. The scales were submitted to 10 field experts for taking opinions for validity. After taking expert opinions, the scales were applied to 56 senior students who used the SIDES in an experimental condition in an academic term within the scope of the teaching practice classes in Sakarya University Computer and Instructional Technologies Teaching Bachelor Program. To examine the construct validity of the scales, the Exploratory Factor Analyses was used. Cronbach's Alpha internal consistency coefficients were calculated for internal consistency reliabilities. As a result of the analyses, one-factor, 6-item "SIDES Satisfaction Scale"; 3-factor, 14-item "SIDES Acceptance Scale" and 3-factor, 19-item "SIDES Usability Scale" were developed. These scales may be used or considered as examples for examining the effectiveness of web-based monitoring and support systems. Keywords: Measurement scales; satisfaction; TAM; teacher candidate; usability.